Adsorption and equilibrium adsorption modeling of bivalent metal cations on viscose rayon succinate at different pHs - Khasbaatar, A. Dashkhuu; Ko, Young Gun; Choi, Ung Su (ELSEVIER, 2007)
A viscose rayon succinate (VRS) was studied as a chelating fiber for the removal of metal ions from an aqueous solution. VRS was synthesized successfully from viscose rayon (VR) and succinic anhydride in the presence of dimethylsulfoxide (DMSO), and was characterized by C-13 nuclear magnetic resonance C-13 NMR, scanning electron microscopy (SEM), and Fourier transform infrared (FT-IR) analysis. The maximum bivalent metal ion adsorption capacity of the VRS was 6.2 meq/g. Studies on the adsorption behaviour of VRS and its ability to remove bivalent trace metals such as Cu2+, Zn2+ Pb2+, and Ni2+ from an aqueous solution were performed both by FT-IR and quantitative analyses at different pHs. The results showed that the adsorption of metals on VRS increased as pH increased, and furthermore, that the adsorption capacity of metal ions could be classified as Cu2+ > Zn2+. > Ni2+ > Pb2+. The adsorption modeling for the interpretation of empirical data was carried out by assuming a probability factor, P(A), and a degree of protonation, chi. Surface potential, psi(0), and an ratio of surface equilibrium constants, K-effect, were obtained using the model. (C) 2007 Elsevier Ltd. All rights reserved.